2022
DOI: 10.1186/s12962-022-00341-8
|View full text |Cite
|
Sign up to set email alerts
|

Hospital efficiency measurement in the west of Iran: data envelopment analysis and econometric approach

Abstract: Objective Measuring hospital efficiency is one of the way how to use resources.The optimal hospital performance is the goals of healthcare policymakers. This study aimed to the current study was conducted to evaluate the efficiency the current study was conducted to evaluate the efficiency and assess the association between hospital size and hospital area population with technical efficiency in public hospitals. Methods In this descriptive-analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
(23 reference statements)
1
7
0
Order By: Relevance
“…While others detailed the model as Radial, Non-Radial and Oriented, Non-Radial and Non-Oriented, and Radial and Non-Radial [23,126]. The majority of the research that were included used Radial DEA models (72 of 89, 80.90%) [46,4852,5462,6577,79,80,8286,89–94,96100,102–116,118124,127130]. BCC, CCR or combination of both models were the specific model utilized in measuring efficiency via radial change of input and output values.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While others detailed the model as Radial, Non-Radial and Oriented, Non-Radial and Non-Oriented, and Radial and Non-Radial [23,126]. The majority of the research that were included used Radial DEA models (72 of 89, 80.90%) [46,4852,5462,6577,79,80,8286,89–94,96100,102–116,118124,127130]. BCC, CCR or combination of both models were the specific model utilized in measuring efficiency via radial change of input and output values.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, either output expansion or input decrease is the primary evaluation goal. More than half of the studies (55.06%, 49 of 89) [4648,5054,58,60,6469,7173,7577,80,9194,96,98,99,103107,109111,113–116,118,121,124,127,128,130,135] applied input-orientated DEA models. The researchers indicated that the choice of input orientation was made to be in line with the fact that the majority of healthcare units aim to minimize inputs given a goal level of output.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DEA is widely applied in healthcare assessment, including hospitals [ 48 ] and health directives [ 49 ]. The choice of model typically corresponds to the researcher’s definition of efficiency [ 15 ].…”
Section: Methodsmentioning
confidence: 99%